2020
DOI: 10.1080/19336950.2020.1788355
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis and review of recent researches on TRPM7

Abstract: The transient receptor potential melastatin-subfamily member 7 (TRPM7) is a ubiquitously expressed protein that contains both an ion channel and an active kinase. TRPM7 has involved in a variety of cellular functions and critically participates in various diseases mainly including cancer and neurodegenerative disorders. However, the theme trends and knowledge structures for TRPM7 have not yet been studied bibliometrically. The main purposes of this research are to compare the scientific production in the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Actually, search results in WoS are not presented by author, year, subject and document types like Scopus, but also by institutions and countries [ 32 ], which is convenient for scholars to analyze the distribution of the research organizations. Moreover, WoSCC has been used as a data source in some previous bibliometric studies [ 33 , 34 , 35 , 36 , 37 , 38 ], which further proves its feasibility especially in the natural science domains. The study design was shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 92%
“…Actually, search results in WoS are not presented by author, year, subject and document types like Scopus, but also by institutions and countries [ 32 ], which is convenient for scholars to analyze the distribution of the research organizations. Moreover, WoSCC has been used as a data source in some previous bibliometric studies [ 33 , 34 , 35 , 36 , 37 , 38 ], which further proves its feasibility especially in the natural science domains. The study design was shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 92%
“…This hypothesis is reinforced by the fact that an overexpression and/or activation of the Mg chanzyme channel, the transient receptor potential cation channel, subfamily M, member 7 (TRPM7), has been found in numerous cancers 17 24 . Based on these studies, therapeutic strategies with anti TRPM7 drugs have been designed in cancer patients 17 , 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…TRPM7 has been cloned and functionally characterized two decades ago [ 1 , 2 , 3 ]. Since then, extensive investigations have been conducted to clarify the molecular and organismal aspects of the TRPM7 function [ 4 ]. The outcome of these studies has been comprehensively discussed in a number of recent review articles [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%